2015
DOI: 10.1111/joop.12130
|View full text |Cite
|
Sign up to set email alerts
|

Resource‐based interventions in the workplace: Integration, commentary, and recommendations

Abstract: We discuss this issue's six articles regarding resource-based interventions in the workplace. Despite some encouraging findings, overall these articles provide weak and inconsistent support for the view that such interventions yield benefits. In particular, the documented benefits are mostly confined to self-reports and lack objective evidence. Future studies of such interventions might find better results by trying different research methods (as some articles have proposed) and by trying different interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Resources based interventions are useful tools to improve people’s work experience. However, as other researchers have highlighted ( Baumeister and Alghamdi, 2015 ), this kind of interventions need to be adjusted to a specific target. Therefore, although we have seen that supervisor support does not moderate the mediation model we tested with truckers, it represents a powerful resource that might contribute to the well-being of workers of others sectors/job positions.…”
Section: Discussionmentioning
confidence: 99%
“…Resources based interventions are useful tools to improve people’s work experience. However, as other researchers have highlighted ( Baumeister and Alghamdi, 2015 ), this kind of interventions need to be adjusted to a specific target. Therefore, although we have seen that supervisor support does not moderate the mediation model we tested with truckers, it represents a powerful resource that might contribute to the well-being of workers of others sectors/job positions.…”
Section: Discussionmentioning
confidence: 99%
“…And, as noted by Baumeister and Alghamdi (2015, p. 624), “Meanwhile, though, practitioners cannot generally wait until research has identified what works best. Practitioners need to do the best they can for people who have issues right now.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional workplace wellbeing interventions have focused on individual stress management, but evidence suggests that traditional stress interventions are often ineffective in the long term and do not result in improved organizational outcomes (LaMontagne et al, 2007; Baumeister and Alghamdi, 2015; Vanhove et al, 2016). Stress and wellbeing constitute separate, but related, constructs.…”
Section: Introductionmentioning
confidence: 99%